Chapter Poggio Bracciolini and Coluccio Salutati: The Epitaph and the 1405-1406 Letters - Baldassarri, Stefano Ugo (Atti, 2020)
Manuscript Magliabechiano VIII.1445 of the Biblioteca Nazionale di Firenze seems to be the only witness of an epitaph that Poggio Bracciolini wrote for Coluccio Salutati. Using this concise yet sincere homage to the late chancellor, this essay discusses Poggio's relationship both with him and the other major members of the Florentine humanist circle that started gathering around Salutati in the late fourteenth century. In doing so, it touches on such figures as - among others - Niccolò Niccoli and Leonardo Bruni. In particular, some early texts by Bruni (e.g., the Dialogi ad Petrum Paulum Histrum and his letters to fellow humanists dating from the early fifteenth century) are seen against the backdrop of his relationship with both Poggio and Salutati.